Whole-genome characterization of halotolerant Enterobacter roggenkampii OSNO4 and its potential for climate-resilient agriculture - Sanjoy Kumar Mukharjee; Md. Faruk Hasan; Biswanath Sikdar (PLoS ONE, 2026)
Plant growth-promoting rhizobacteria (PGPR) represent an eco-friendly strategy to improve crop yield under abiotic stress conditions. This study aimed to perform a comprehensive genomic and functional profiling of a halotolerant rhizobacterium to evaluate its multi-trait plant growth-promoting (PGP) potential and its precise contribution to mitigating salinity stress for climate-resilient agriculture. In the present study, 24 (8.5%) rhizobacterial isolates showed phosphate-solubilizing activity out of 283 isolated bacteria from rice rhizosphere. From these, strain OSNO4 was selected for detailed evaluation. The isolate demonstrated phosphate solubilization (solubilization index: 1.22) and potassium solubilization, indole-3-acetic acid (IAA) production (38.34 µg/ml), nitrogen fixation, siderophore and ammonia production, protease activity, and biofilm formation in vitro . Additionally, it showed tolerance to salinity (10% NaCl), drought (20% PEG 6000), temperature (45 °C), and a broad pH range. Strain OSNO4 further suppressed the growth of phytopathogenic fungi Fusarium concentricum by 54.23%. Whole-genome sequencing analysis identified the strain as Enterobacter roggenkampii (ANI 98.2%, dDDH 85.7%), with a 4.67 Mb genome harboring total 4,546 predicted genes and diverse functional subsystems. Comprehensive genomic study further revealed the presence of genes linked to nutrient mobilization, phytohormone biosynthesis, abiotic stress tolerance, and antifungal activity. Six biosynthetic gene clusters, including siderophore-related and putatively novel clusters were also identified. Pan-genome analysis revealed an open genome structure with high flexibility and genetic variability. Under salinity stress, OSNO4 inoculation significantly improved rice seed germination (52.22% to 85.56% at 100 mM NaCl; 42.22% to 72.22% at 150 mM NaCl), root and shoot development, and biomass accumulation compared to uninoculated controls. The strain also showed broad antibiotic susceptibility and non-hemolytic phenotype, suggesting its biosafe nature. In summary, these data demonstrate that E. roggenkampii OSNO4 possesses a robust repertoire of genomic determinants and functional capabilities, establishing it as a highly potent bioinoculant for deployment in climate-resilient and sustainable agroecosystems.